Entrepreneurship Learning Model to Improve the Competence of Vocational Students at the Islamic University of Indonesia - Istiningsih, Istiningsih (Dinamika Ilmu, 2020)
Entrepreneurship is one of the spearheads of the economy so it is important to provide entrepreneurship education and one of them is in higher education. With entrepreneurship education, students create jobs and reduce the numbers given. The purpose of this study is to develop an effective entrepreneurship learning model by analyzing the role of lecturer experience and internship programs on student entrepreneurial competencies. The research method used is quantitative research with primary data based on the results of research in the field using instruments such as rt to partially or simultaneously test the developed model. The results of the research, the experience of lecturers in carrying out entrepreneurial activities and industrial internship programs for students partially or simultaneously have a positive effect on the competence of students in the vocational department of the Islamic University of Indonesia.